Gamification Analytics Model for Teachers - Tenório, Kamilla; Dermeval, Diego; Silva, Alan Pedro da (Anais Estendidos do Congresso Brasileiro de Informática na Educação (CBIE), 2020)
Despite the growing interest in applying gamification in the technology-enhanced learning context, previous studies have reported unexpected results concerning students' engagement, learning outcomes, and motivation in gamified learning systems. A possible solution to avoid these unexpected outcomes is the use of the gamification analytics approach, that is the data-driven process of monitoring and adapting gamification designs. Therefore, this dissertation proposes a gamification analytics model for teachers. In this model, the teacher defines interaction goals, monitor students' interaction with the learning resources and the gamification elements, and adapt the gamification design through missions for students that are not achieving the goals. A gamification analytics model-based tool, GamAnalytics, was developed, implementing the most well-rated design concepts validated by teachers through a speed dating method. Teachers evaluated the developed tool where perceived usefulness, perceived ease of use, behavioral intention, relevance, perceived enjoyment, and self-efficacy metrics were measured, and results showed a high acceptance and approval of the tool. Furthermore, to investigate the impact of the use of gamification analytics model by teachers through the GamAnalytics tool on students, a case study was conducted. The results suggest an improvement in students engagement, learning outcomes, and a positive effect on students motivation.